2020
DOI: 10.3389/fmars.2020.00646
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Year Density Variation of Queen Conch (Aliger gigas) on Serrana Bank, Seaflower Biosphere Reserve, Colombia: Implications for Fisheries Management

Abstract: BACKGROUND Queen conch Aliger gigas (Linnaeus, 1758), formerly known as Strombus gigas, constitute a valuable commercial and cultural resource for native communities since pre-Hispanic times (Baisre, 2010). Populations of this marine gastropod are registered for 36 countries in the Caribbean, extending from Florida to the northern coast of South America and live mainly on sandy bottoms, in clear waters down to a depth of 100 m (CITES, 2003). Mating and spawning usually take place during the warmer months of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Strombidae is one of the most familiar molluscan groups composed of about 100 species that mostly live in sand, seagrass, and mud flats area, and they are considered the source of food in many tropical and subtropical regions all over the world (Oo 2018;Ardila et al 2020). However, Strombidae is affected by overexploitation caused by both natural and anthropogenic stressors, which leads to a large Natsir and Dillenia 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strombidae is one of the most familiar molluscan groups composed of about 100 species that mostly live in sand, seagrass, and mud flats area, and they are considered the source of food in many tropical and subtropical regions all over the world (Oo 2018;Ardila et al 2020). However, Strombidae is affected by overexploitation caused by both natural and anthropogenic stressors, which leads to a large Natsir and Dillenia 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the identified gastropods, include C. urceus, M. annulus annulus, C. viridis, C. capitaneus, T. sparverius, N. undata, were commonly harvested in muddy-sandy and sandy-coralline substrates in the coastal area. However, the T. sulcata and I. obsolete were commonly harvested in the H' = -∑ P i (ln P i ) decrease in the population of marine species (Stoner et al 2018;Ardila et al 2020). There are about 13 genera of Strombidae, with more than 50 different species reported that are found in the Philippines (Poppe 2008a(Poppe , 2008b, and these include the C. urceus (Pangarungan et al 2022) mangrove area of Guang-guang.…”
Section: Abundance Of Gastropodsmentioning
confidence: 99%
“…This family of marine gastropods comprises about 100 species worldwide, which are found in tropical to subtropical, mainly living in shallow water, on sandy, muddy, rubble bottoms, or on marine grass flats (Poutiers, 1998). These species are considered a popular food source in many tropical and subtropical regions all over the world (Oo, 2018;Ardila et al, 2020) and of local economic importance (Poutiers, 1998). Over the years, most Strombidae species have been victims of intensive overfishing, which led to a declining population that resulted in large-scale exploitation of the species (Ponder and Lindberg, 1997;Stoner et al, 2018;Ardila et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These species are considered a popular food source in many tropical and subtropical regions all over the world (Oo, 2018;Ardila et al, 2020) and of local economic importance (Poutiers, 1998). Over the years, most Strombidae species have been victims of intensive overfishing, which led to a declining population that resulted in large-scale exploitation of the species (Ponder and Lindberg, 1997;Stoner et al, 2018;Ardila et al, 2020).…”
Section: Introductionmentioning
confidence: 99%